APLIKASI TEKNOLOGI TEPAT GUNA PENINGKATAN PRODUKTIFITAS MINYAK SERAI WANGI: APLIKASI TEKNOLOGI TEPAT GUNA PENINGKATAN PRODUKTIFITAS MINYAK SERAI WANGI - Yufrizal Yufrizal; Abd Aziz; Nofri Helmi (Jurnal Vokasi Mekanika (VoMek), 2020)
The purpose of this activity is to increase the productivity of lemongrass oil in Kampung Dalam village. Lemongrass is one type of essential oil plant, which is classified as developed. The results of the distillation of the leaves are obtained by citronella oil which is known in the trading world as Citronella Oil. The method applied to this community service activity is an approach to the community. Provides insight into TTG that can be applied to the refining of citronella oil. Furthermore, about the importance of steam-producing boilers for distillation. This process requires wood fuel and a good installation system, so that the yield can be increased. Applying appropriate technology for refining citronella oil. The solution to partner problems that will be carried out in community service activities is to manufacture a relatively large size signaling kettle. The capacity of the distillation catel to be made is 40 Kg. In this activity the community service team also applied technological innovations to the kettle. The material to be used is a stenless steel plate. The kettle will also be equipped with a water control indicator and boiler pressure. With the improvement and implementation of technology in this boiler, it is hoped that the productivity of lemongrass oil in the village will be superior and can improve the welfare of the community.